Trade and tourism in Democratic Republic of Congo: Key business for sustainable financing - Nadine Mujinga Kuka; Jinhwan Oh; Jisun Song (Global Business & Finance Review (GBFR), 2021)
Purpose: This study examines Democratic Republic of Congo's (DRC) trade and tourism as the country's key business for sustainable financing and growth. Design/methodology/approach: This study uses a panel dataset of DRC's trade and tourism flows from 165 countries over two years (2014-2015). An empirical analysis based on the gravity model is conducted. Findings: The empirical results are basically consistent with the general prediction of the gravity model that both size and distance matter, but, this stereotype result seems to fade away when the consumer price index (CPI) and region dummy are added. Research limitations/implications: Based on the results, it is recommended that DRC to take appropriate measures and cooperate with its neighboring African countries to attract more tourists, strengthen existing trade agreements, and implement policies to minimize real exchange volatility and strengthen misalignment to create maximize economic benefits. Originality/value: An empirical paper for DRC, particularly for both trade and tourism is rare. This study is expected to give a guideline for this country's sustainable growth.
Keywords: 650; Democratic Republic of Congo; Trade; Tourism; Regional Integration; Gravity Model